Risk weights, lending, and financial stability: Limits to model-based capital regulation - Markus Behn; Rainer Haselmann; Vikrant Vig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Model-based capital regulation is considered to be one of the key innovations of Basel II. The objective of this innovation was to make capital charges more sensitive to risk. Using data from the German credit register, and employing a difference-indifference identification strategy, we empirically investigate how the introduction of this regulation affected the quantity and the composition of bank lending. We find that credit supplied by banks that introduced the model-based approach exhibits a higher sensitivity to model-based PDs as compared with credit supplied by banks that remained under the traditional approach. Interestingly, however, we find that risk models used for regulatory purposes tend to underpredict actual default rates. There is no such prediction error in PDs for loans under the traditional approach.
Keywords: G01; G28; G21; 330